Students’ Writing Anxiety Levels, Types, and Causes in Writing Undergraduate Thesis Proposal: A Study at English Language and Literature Department - Hanifah Ummul Khairah; Sitti Fatimah (Universitas Negeri Padang, 2022)
Anxiety in recent years has become a hot issue discussed by many people one of them is foreign language anxiety which includes various anxiety in foreign language aspects. In terms of writing, this anxiety is known as writing anxiety. This research aims to describe the level, type, and causes of writing anxiety of English language and literature department students at UNP in writing Thesis Proposals. This research used a descriptive study involving 70 fourth-year students that have already taken Thesis Proposal Writing class and are currently writing their thesis proposals. Through random sampling technique, 14 students (20% of the population) were selected. Data were collected through the SLWAI (Second Language Writing Anxiety Inventory) questionnaire adapted from Cheng (2004) and interview sessions. The results showed that students experienced anxiety at the medium level with cognitive anxiety being the most dominant type. Other results are four main factors that cause writing anxiety in writing a thesis proposal. They are low self-confidence, language difficulties, insufficient writing technique, and pressure for perfect work.